Asfixia Neonatal: incidencia y mortalidad en•el Hospital de Apoyo Nº 02 Yarinacocha, " Pucallpa" Período Octubre 1993 w Mayo' 1994 - Ramírez Rivera, Rosa: Dorita (1995)
A study applied explanatory level in Support Hospital NQ 02 Yarinacocha, Pucallpa in the period October 1 of 1,993 was conducted - 30 May 1,994, finding 665 live births that make my sample universe; loa which 74 were for infants with Apgar less than 7 per minute, according to the inclusion criteria; in order to determine the incidence of neonatal asphyxia, identify predisposing factors, immediate complications of newborn asphyxia and neonatal mortality rate. The incidence of neonatal asphyxia found is high compared to loe findings by other authors. Loa predisposing factors were identified, being the most significant; lower maternal age of 19 years and more than 36 years, no prenatal care, primiparous and multiparous great, anemia, premature rupture of membrane, toxemia, obstructed labor, gestational age less than 36 weeks and more than 42 weeks, breech presentation and cephalopelvic inconsistency as grounds for neonatal asphyxia. The complications presented were asphyxiated newborns in relation to the intensity of the previous obstetric asphyxia and resuscitation in the delivery room. The neonatal mortality rate is almost similar to that reported by other studies